Gambaran Gaya Hidup Pada Penderita Hipertensi di Puskesmas II Denpasar Barat - Damayanti, Ni Made Ayu; Suardana, I wayan; Manafe, Neil Oktovianus; Putra, I Gede Yudiana (Akademi Keperawatan Kesdam IX/Udayana, 2019)
ABSTRACT Background: Hypertension has now become a global problem because its prevalence continues to increase along with lifestyle changes that include unhealthy habits. the aim is to find out a description of lifestyle in hypertensive patients in West Denpasar Health Center II. Method: The study design was descriptive with the Cross Sectional approach. The sample in this study were all hypertensive patients who were treated at the Denpasar Public Health Center II. The sampling technique is Acidental sampling with a sample of 46 respondents. The research instrument used was a questionnaire sheet. The results of data processing are presented in narrative form, frequency distribution tables are accompanied by interpretations. Results: Hypertension sufferers in West Denpasar Health Center II were 27 respondents (58.7%) who did not have the habit of consuming excess salt; 26 respondents (56.5%) who did not have coffee consumption habits; 34 respondents (73.9%) who did not have the habit of consuming liquor; 32 respondents (69.6) did not have smoking habits; 26 respondents (56.5%) respondents did not have enough hours of rest / sleep; respondents who do sufficient activities / sports; 46 respondents as many as 25 respondents (54.3%) obeyed taking drugs; 25 respondents (54.3%) did not routinely carry out tension control; 30 respondents (65.2%) faced maladaptive stressors. Conclusion: To reduce the incidence of hypertension in patients with hypertension, health promotion programs to the public regarding hypertension factors need to be optimized.   Keywords: Hypertension; Lifestyle   ABSTRAK Latar belakang: Hipertensi kini sudah menjadi masalah global karena prevalensinya yang terus meningkat sejalan dengan perubahan gaya hidup yang meliputi kebiasaan-kebiasaan tidak sehat. tujuannya untuk mengetahui gambaran gaya hidup pada penderita hipertensi di Puskesmas II Denpasar Barat. Metode: Desain penelitian adalah deskriptif dengan pendekatan Cross Sectional. Sampel pada penelitian ini adalah seluruh pasien hipertensi yang berobat di Puskesmas II Denpasar. Teknik sampling adalah Acidental sampling dengan jumlah sampel 46 responden. Instrument penelitian yang digunakan adalah lembar kuisioner. Hasil pengolahan data disajikan dalam bentuk narasi, tabel distribusi frekuensi disertai dengan interpretasi. Hasil: Penderita hipertensi di Puskesmas II Denpasar Barat sebanyak 27 responden (58,7%) yang tidak memiliki kebiasaan mengonsumsi garam berlebih; 26 responden (56,5%) yang tidak memiliki kebiasaan mengonsumsi kopi; 34 responden (73,9%) yang tidak memiliki kebiasaan mengonsumsi minum-minuman keras; 32 responden (69,6) tidak mempunyai kebiasaan merokok; 26 responden (56,5%) responden tidak memiliki jumlah jam istirahat/tidur yang tidak cukup; responden yang melakukan aktifitas/olahraga yang cukup; 46 responden sebanyak 25 responden (54,3%) taat mengonsumsi obat; 25 responden (54,3%) tidak rutin melakukan kontrol tensi; 30 responden (65,2%) menghadapi stresor secara maladaptif. Simpulan: Untuk menekan kejadian hipertensi pada penderita hipertensi  maka program promosi kesehatan kepada masyarakat  mengenai faktor-faktor hipertensi perlu dioptimalkan. .